Social Well-Being and Its Related Areas in Older People Living in Nursing Homes - Arezoo Mirzazadeh; Abdolhosein Emami Sigaroudi; Mohammad Taghi Moghaddamnia; Ehsan Kazemnezhad Leyli; Ali Noori Saeed (Journal of Holistic Nursing and Midwifery, 2019)
Introduction: The surge in the aging population is a global phenomenon. Thus, it calls for attention to the issue of health, comfort, and welfare of the elderly in different aspects including Social Well-being (SW). Objective: In this regard, this study aims to investigate the SW status and its related areas in the elderly people living in nursing homes of Rasht City, Iran with respect to socio-demographic variables. Materials and Methods: This cross-sectional study was conducted on 185 elderly aged over 60 years living in the nursing homes in Rasht. Sampling was done by census method. Data collection tools were socio-demographic form and the Iranian social well-being questionnaire. For analyzing data, descriptive statistics and statistical tests of Mann-Whitney, Kruskal-Wallis, and logistic regression analysis were used. Results: The Mean±SD SW score of the participants was 4.64±0.91 (from 5), where the highest score was in the area of family, and the lowest in the area of friend/relative. The SW status of the majority of subjects in the area of family was “good” (56.2%); in the area of friend/relative, was “poor” (53.5%); and in the area of community, was “moderate” (63.8%). On the whole, the SW status of most subjects was moderate (56.2%). Among socio-demographic variables, the type of nursing home (OR=2.8, P<0.024), and receiving phone calls (once a week) (OR=19.7, P<0.0001) were predictors of SW. Conclusion: Considering the specific structure of Iranian families and the importance and position of the elderly, their SW score in the field of family is not appropriate, and there is still room for concentration on the family along with the community. Also, outside-family communications of the elderly people need more attention and should be considered in planning and care of this age group.